GENERALIZATION THE RESULTS OF THE ENSURING ANALYSIS THE SUSTAINABLE DEVELOPMENT GOALS OF THE UN MEMBER STATES - Khymchak , V. (Theory and Practice of Public Administration, 2021)
According to the results of analytical reports [7], which are presented on the collected and assessed data in 2019, information on ensuring the sustainable development goals indicates that already about 150 countries of the world have developed national policies to address the challenges of rapid urbanization, 71 countries and the European Union now have over 300 policies and tools to support sustainable consumption and production. And a wide range of other actors - international organizations, business, local authorities, academia and civil society - are collaborating to achieve and secure sustainable development goals.The article summarizes the results of the ensuring analysis the sustainable development goals of the UN member states based on the monitoring assessments results in the documentary reports of the UN and the EU. It has been established that: the reduction in the incidence of extreme poverty in the world continues, but its pace has slowed down; increased investment in infrastructure and technology for sustainable agricultural production is needed; a concerted effort is needed to achieve universal health coverage and sustainable health financing; much more actively introduce renewable energy sources, including in the field of transport and heat supply; expand employment opportunities and decent work for all; extend the duty-free regime for exports from least developed countries and developing countries and increase aid to least developed countries and small island developing States; take urgent measures to meet modern material needs, so that this does not lead to overexploitation of resources and environmental degradation; expand protected areas for the conservation of marine biodiversity, as well as existing policies and treaties that encourage the responsible use of oceans, the protection of terrestrial ecosystems and biodiversity; scale up efforts to accelerate progress towards building national human rights institutions consistent with the Paris Principles; and continue to expand international cooperation.